The Influence of Online Customer Reviews and Online Customer Ratings on Purchasing Decisions on the Lazada Marketplace (Study of FISIP Students, University of Riau Using the Lazada Application) - Sari, Renna Selviana; Othman, Lie (Journal Of Accounting Management Business And International Research, 2024)
The development of technology and the internet has changed the consumer paradigm in making purchases, especially through online platforms such as Lazada. This research aims to examine the influence of online customer reviews and ratings on purchasing decisions on the Lazada marketplace, with a focus on students at the Faculty of Social and Political Sciences, University of Riau who use the Lazada application. The research method used was a survey via questionnaire distributed to 300 student respondents. Data analysis was carried out using multiple linear regression techniques to test the research hypothesis. The research results show that online customer reviews and online customer ratings have a significant influence on purchasing decisions at Lazada. This shows that online customer reviews and ratings play an important role in shaping buyers' perceptions of the products offered on the platform.